2015
DOI: 10.1155/2015/645984
|View full text |Cite
|
Sign up to set email alerts
|

Krill Oil Ameliorates Mitochondrial Dysfunctions in Rats Treated with High-Fat Diet

Abstract: In recent years, several studies focused their attention on the role of dietary fats in the pathogenesis of hepatic steatosis. It has been demonstrated that a high-fat diet is able to induce hyperglycemia, hyperinsulinemia, obesity, and nonalcoholic fatty liver disease. On the other hand, krill oil, a novel dietary supplement of n-3 PUFAs, has the ability to improve lipid and glucose metabolism, exerting possible protective effects against hepatic steatosis. In this study we have investigated the effects of kr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…In this context, OO consumption is encouraged, as it has been associated to a lower prevalence of chronic diseases and hepatic disorders (Sofi & Casini, ; Velasco et al ., ). On the other hand, KO has become increasingly popular because of its capability of reducing hepatic lipogenesis, stimulating catabolism of fat excess introduced by a HF diet and ameliorating mitochondrial function (Ferramosca et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In this context, OO consumption is encouraged, as it has been associated to a lower prevalence of chronic diseases and hepatic disorders (Sofi & Casini, ; Velasco et al ., ). On the other hand, KO has become increasingly popular because of its capability of reducing hepatic lipogenesis, stimulating catabolism of fat excess introduced by a HF diet and ameliorating mitochondrial function (Ferramosca et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…We also found that fatty acid composition of the diet was able to influence the activity of some enzymes of the Krebs cycle, such as CS, aconitase and fumarase. A strong and significant negative correlation of CS with obesity was reported in liver (Ferramosca et al ., ) and in human omental adipose tissue (Christe et al ., ). At the same time, an increase in CS activity was recently observed after KO diet supplementation in rat liver (Ferramosca et al ., ), suggesting that a modulation of the activity of this protein, which is the rate‐limiting enzyme of the Krebs cycle, could regulate the flux of reducing equivalents to mitochondria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that citrate synthase activity was suppressed in obese mice, resulting in excessive carbon flow into the citrate cycle prompting energy storage [44]. Gut microbiota appears to play a key role in the development and progression of obesity, together with changes in citrate synthase activity [45, 46]. In this study, analysis of the results of whole microbial genome sequencing suggested that enrichment in the microbial function that relates to citrate cycle was significantly different between the fat and lean lines (Fig.…”
Section: Discussionmentioning
confidence: 99%